168PA retrospective multicenter study evaluating the efficacy and safety of irinotecan in patients with advanced gastric cancer: Analysis of Glasgow Prognostic Score (GPS). (24th November 2019) - Honda, T; Nakano, S; Yuki, S; Sawada, K; Muranaka, T; Kawamoto, Y; Nakatsumi, H; Yoshita, H; Ando, T; Harada, K; Kobayashi, Y; Miyagishima, T; et al.
Abstract: Background: It is important to predict prognosis in patients with advanced gastric cancer receiving chemotherapy. Several studies have reported that Glasgow prognostic score (GPS), which was based on serum albumin (Alb) and C-reactive protein (CRP), was associated with poor prognosis in many cancers. However, it is unclear whether GPS has prognostic value when patients receive Irinotecan, which is a key drug of advanced gastric cancer. Methods: We conducted a retrospective multicenter study and investigated association between efficacy and GPS in patients who received irinotecan monotherapy between January 2010 and December 2017. All patients had to receive fluoropyrimidine and platinum as prior therapy. GPS was identified that GPS 0 was CRP ≤1.0 mg/dL and Alb ≥3.5 g/dL, GPS 1 was CRP >1.0 mg/dL or Alb <3.5 g/dL, and GPS 2 was CRP >1.0 mg/dL and Alb <3.5 g/dL. Results: There were 174 patients at 8 centers included in this study. The number of patients with GPS 0/1/2 was 76/56/42, respectively. In GPS 0/1/2 patients, performance status (0-1/2≤), treatment line 2 nd /3 rd or later, and HER2 status were significantly different among them(p < 0.01). As for safety, there was no significant difference among GPS 0/1/2 patients. In GPS 0/1/2 patients, median PFS were 3.7/2.8/2.0 months (p < 0.01), median OS were 11.9/7.2/6.7 months (p < 0.01), respectively. In multivariate analysis, GPS was associated with shorter PFS (GPS 0 vs 1/0vs 2 : HR 1.180/2.378, 95%C.I. 0.793-1.758/1.405-4.024, p = 0.414/0.001), and shorter OS (GPS 0 vs 1/0vs 2 : HR 1.520/2.529, 95%C.I. 1.002-2.305/1.518-4.213, p = 0.049/<0.001). Conclusions: In this analysis, GPS might be a predictive and prognostic factor in treatment with irinotecan monotherapy for patients with AGC. Legal entity responsible for the study: Yoshito Komatsu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.